The Effect of Earning Persistence, Company Size, and Capital Structure on the Earning Response Coefficient - Mohamad Zulman Hakim; Virania Aulia; Hamdani Hamdani; Imam Hidayat; Dirvi Surya Abbas; Januar Eky Pambudi (Cita konsultindo, 2022)
The purpose of this study is to determine the effect of earnings persistence, company size, and capital structure on the Earning Response Coefficient in property and real estate sector companies listed on the IDX in 2019 – 2021. In several previous studies regarding the Earning Response Coefficient, it has several limitations, such as a lack of independent variables, using the same independent variables, and so on. So this study uses other variables such as earnings persistence, company size, and capital structure. Sampling in this study using purposive sampling method, which can produce a sample of 17 companies of 82 companies obtained from the results of eliminating the sample criteria. Methods of data analysis using Panel Data Regression Analysis. The results of this study indicate that earnings persistence and firm size have no effect on the Earning Response Coefficient. While the capital structure has a positive influence on the Earning Response Coefficient.